Low incidence of cannibalism among brood parasitic cuckoo catfish embryos - Zimmerman, Holger; Tolman, Deryk; Reichard, Martin (Behavioral ecology, 2023)
Brood parasites have demanding needs of host resources. Brood parasitic offspring are highly competitive and frequently cause the failure of host broods and the survival of a single parasitic offspring. Accordingly, virulent brood parasites lay a single egg in the same host nest to avoid sibling competition. In the cuckoo catfish (Synodontis multipunctatus), which parasitize mouthbrooding cichlid fishes in Lake Tanganyika, the modes of host and parasite oviposition lead to frequent cases of multiple parasitism. We experimentally tested the prediction that multiple parasitism leads to frequent cannibalism among offspring. Cuckoo catfish embryos prey upon host offspring to obtain nourishment during their 3-week development in the host buccal cavity and may also consume conspecific embryos. The potential benefits of cannibalism in the system are, therefore, twofold; to decrease competition for limited resources (i.e., host brood with rich yolk sacs) and to directly obtain nourishment by consuming rivals. We found that cannibalism indeed provided measurable benefits in terms of increased growth of the cannibals, but cannibalism was rare and typically occurred once all host offspring had been consumed. This implies that cannibalism among cuckoo catfish embryos emerges to mitigate starvation rather than eliminate competition.
Keywords: embryo predation; cichlid fish; sibling competition; brood parasitism; siblicide; mouthbrooding